Reducing Stunting Through Specific Nutrition Interventions in Action to Prevent Stunting Program (ACS) and Supplementary Feeding Program (PMT) - Nurlailis Saadah; Dwi Indah Cahyaningsari; Nana Usnawati; Nuryani (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Stunting is one of the nutritional problems that is a priority and must be addressed. Specific nutrition interventions in the ACS and PMT programs both have an effect on reducing stunting. Objective: To find out the differences in the effect of specific nutrition interventions in the ACS and PMT programs on reducing stunting. This research is a comparative research, cross-sectional research design. Sample: This study consisted of 60 stunted toddlers, consisting of 30 stunted toddlers in Jabung Village ad 30 stunted toddlers in Ngiliran Village. Analysis of differential effects: Independent Sample t-test. Results showed that specific nutrition interventions in the ACS program showed that 15% of toddlers passed stunting and 35% of toddlers did not pass stunting, while during the PMT implementation, 10% of toddlers passed stunting and 40% of toddlers did not pass stunting. The Independent Sample t-test concluded that there were differences in the effect of specific nutrition interventions on the ACS and PMT programs on stunting reduction. Concluded tha there were differences in the effect of specific nutrition interventions in the ACS and PMT programs had an effect on reducing stunting. So it is suggested that the handling of stunting in the ACS program can be disseminated and replicated on other places to reduce the incidence of stunting.